The Village Of BATTIR Resort - SHRAIM, ZAHRA (My University, 2022)
Battir Village Resort As Battir is in the World’s Heritage list the main concept of the project is to combine the site needs of tourism development and to develop the economic status of the city plus creating all of this without ruining the natural site and components. To make this project a way for the people to get out of their busy life to the countryside environment. The project tends to create a naturalistic environment and bring people close to nature. And use of local available and eco-friendly material to put less impact on the natural environment.